Functional growth analysis of diploid potato varieties (Solanum tuberosum Phureja group) (2023)
The growth analysis is relevant to understanding and comparing in terms of physiological and productive behavior varieties. The study aims to determine the accumulation and distribution of dry matter through different phenological stages of development in four diploid potato varieties. For this, in a randomized complete block design with three replications, four varieties of diploid potato were evaluated: Paola, Violeta, Primavera, and Paysandú. Based on direct measurements of leaf area and dry matter of each organ, it was computed the growth indices of relative growth rate (RGR), net assimilation rate (NAR), leaf area relation (LAR), and source-sink relation. The duration of development stages of flowering, fruit, and tuber development was measured in terms of thermal time. Furthermore, the number of stems, stolons, and tubers was measured, and the yield was registered at the cycle end. The varieties Paola and Primavera reached a greater accumulation of dry matter in each organ and a greater number of tubers by plant about the varieties Paysandú and Violeta. The organs with the greater biomass accumulated were the leaves, stems, and tubers. The source and demand power had a considerable correlation between the NAR and RGR, which increased toward the end of the cycle for Paola and Primavera varieties. The yield and the beginning and duration of the growth stages were related to the season and the varieties.